STOMACH TARGETED MUCOADHESIVE DRUG DELIVERY OF OFLOXACIN - MAHESWARAPPA CHATTER; S. A. SREENIVAS (International Journal of Pharma and Bio Sciences, 2016)
The Present study concerns the development and characterization of stomach targeted mucoadhesive tablets of ofloxacin in order to prolong the gastric residence time after oral administration. Ofloxacin is a synthetic fluoroquinolone antibacterial agent that inhibits the supercoiling activity of bacterial DNA gyrase, halting DNA replication and effective against both the gram positive and gram negative bacteria. Different types of polymers such as sodium carboxymethylcellulose, carbopol934P, hydroxypropylmethylcellulose K4M and polyethylene glycol 6000 were used to formulate the mucoadhesive tablets. The tablets were prepared by direct compression technique and were evaluated for parameters such as weight variation, drug content, thickness, hardness, surface pH, in vitro mucoadhesive strength, swelling index, and in vitro drug release. All the parameters evaluated for all formulations were satisfactory. Among all formulations, F3 with combination of carbopol934P and sodium carboxymethyl cellulose showed greater in vitro drug release of 98.86 after 24 hrs, better mucoadhesive strength and good swelling. Hence formulation F3 was optimized and the stability studies were carried out according to ICH guideline which showed that the formulation F3 was stable.